2003
DOI: 10.5194/acp-3-2225-2003
|View full text |Cite
|
Sign up to set email alerts
|

Weekly cycle of NO<sub>2</sub> by GOME measurements: a signature of anthropogenic sources

Abstract: Abstract. Nitrogen oxides (NO+NO 2 =NO x and reservoir species) are important trace gases in the troposphere with impact on human health, atmospheric chemistry and climate. Besides natural sources (lightning, soil emissions) and biomass burning, fossil fuel combustion is estimated to be responsible for about 50% of the total production of NO x . Since human activity in industrialized countries largely follows a seven-day cycle, fossil fuel combustion is expected to be reduced during weekends. This "weekend eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
293
5
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 375 publications
(328 citation statements)
references
References 13 publications
27
293
5
3
Order By: Relevance
“…Our observation agrees with observations by Beirle et al (2003) and Wenig (2001) that no significant NO 2 weekly cycle can be found over Hong Kong from space. However, such a cycle can be observed in the LP-DOAS measurements as well as the EPD data during the morning rush hour (08:30 to 09:30 LT).…”
Section: Daily and Weekly Cycle Of Nosupporting
confidence: 83%
“…Our observation agrees with observations by Beirle et al (2003) and Wenig (2001) that no significant NO 2 weekly cycle can be found over Hong Kong from space. However, such a cycle can be observed in the LP-DOAS measurements as well as the EPD data during the morning rush hour (08:30 to 09:30 LT).…”
Section: Daily and Weekly Cycle Of Nosupporting
confidence: 83%
“…However, the first study that observed pollution WCs from space focused on tropospheric NO 2 (Beirle et al, 2003). Satellite measurements from the Global Ozone Monitoring Experiment (GOME) aboard ERS-2 revealed a clear Sunday minimum with reduced NO 2 tropospheric columns compared to the working-day levels over the US, Europe and Japan.…”
Section: A Sanchez-lorenzo Et Al: Assessing Large-scale Weekly Cyclmentioning
confidence: 99%
“…NO 2 observations from satellite offer a globally consistent data set, albeit at coarse resolutions of 10 s to 100 s of kilometers, enabling a wide range of applications including many not feasible from in situ observations. Several studies have used satellite observations of NO 2 to evaluate chemical transport models (Martin et al, 2002;van Noije et al, 2006;Lamsal et al, 2008;Kim et al, 2009;Herron-Thorpe et al, 2010;Huijnen et al, 2010), examine spatial and temporal patterns of NO x emissions (Beirle et al, 2003;Richter et al, 2005;Kim et al, 2006;van der A et al, 2006;Zhang et al, 2007;Boersma et al, 2008a;Lu and Streets, 2012;Wang et al, 2012;Hilboll et al, 2013;Russell et al, 2010Russell et al, , 2012Duncan et al, 2013), examine NO x sources (Jaeglé et al, 2005;van der A et al, 2008;Bucsela et al, 2010;de Wildt et al, 2012;Lin, 2012;Ghude et al, 2010Ghude et al, , 2013aMebust et al, 2011;Mebust and Cohen, 2013), provide top-down constraints on surface NO x emissions Konovalov et al, 2006;Zhao and Wang, 2009;Lin et al, 2010;Lamsal et al, 2011;Ghude et al, 2013b;Vinken et al, 2014), infer NO x lifetimes (Schaub et al, 2007;Lamsal et al, 2010;Beirle et al, 2011), and estimate surface NO 2 concentrations …”
Section: Introductionmentioning
confidence: 99%